The radiomimetic compound streptonigrin induces persistent telomere dysfunction in mammalian cells - Paviolo, Natalia Soledad (2014)
We analyzed the chromosomal aberrations involving telomeres in the progeny of mammalian cells exposed to the radiomimetic compound streptonigrin (SN) in order to determine if this antineoplastic drug induces long-term telomere instability. To this end, rat cells (ADIPO-P2 cell line, derived from adipose cells from Sprague–Dawley rat) were treated with a single concentration of SN (100 ng/ml), and chromosomal aberrations were analyzed 18 h and 10 and 15 days after treatment by using PNA-FISH with a pan-telomeric probe [Cy3-(CCCTAA)3] to detect (TTAGGG)n repeats. Cytogenetic analysis revealed a higher frequency of telomere dysfunction-related aberrations (additional telomeric FISH signals, extra-chromosomal telomeric FISH signals, and telomere FISH signal loss and duplications) in SN-exposed cultures vs. untreated cultures at every time points analyzed. The yield of SN-induced aberrations remained very similar at 18 h, 10 days as well as 15 days after treatment. Thus, our data demonstrate that SN induces persistent telomere dysfunction in mammalian cells. Moreover, we found that the level of telomerase activity in SN-treated cells was significantly lower (up to 77%) than that of untreated control cells at each time points analyzed. This fact suggests that telomerase could be involved in SN-induced telomere dysfunction.